The Impact of Product Quality and Courier Service Quality on Customer Loyalty, with Customer Satisfaction as Mediator (An Empirical Study of Alfagift Application Users In Greater Jakarta) - Samuel Halim; Liem Bambang Sugiyanto (Journal Research of Social Science, Economics, and Management, 2024)
This study examines the impact of product quality and courier service quality on customer loyalty, with customer satisfaction acting as a mediating variable, within the context of e-grocery applications Alfagift in Indonesia. This study collected 120 samples of Alfagift application users in Greater Jakarta using non-probability based predefined criteria. The Likert scale based questionnaire data was collected and analyzed using structural equation model (SEM) and AMOS software. The result indicates that product quality and courier service quality positively and significantly impact customer satisfaction. Furthermore, both product quality and courier service quality positively and significantly impact customer loyalty. Meanwhile, customer satisfaction acted as a mediation in the relationship between product quality and courier service quality on customer loyalty. The research underscores the importance of quality control and operation efficiencies in enhancing customer satisfaction and retention. Finally, this research serves as a reference and provides insights for businesses aiming to foster customer loyalty.